2007
DOI: 10.1097/bth.0b013e318030a566
|View full text |Cite
|
Sign up to set email alerts
|

Avulsion Injuries of the Nail Bed Do Not Need Nail Bed Graft

Abstract: From 1985 to 1992, 12 cases of severe avulsion injuries of the nail bed were treated by allowing the nail bed to regenerate naturally, without a nail bed graft irrespective of the extent of nail bed loss. This involved simply covering the residual nail bed with the nail splint for a period of approximately 6 weeks or until the nail bed was observed to be fully regenerated. The patients were then followed up until full nail growth. It was observed that the nail bed regenerated spontaneously, followed by a norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Some authors simply insert a nail splint and leave the nail bed under spontaneous healing, without a graft. 26 We strongly believe that a careful and complete reconstruction of all involved structures is the guarantee for the best results. In our experience, in these cases where there is no loss of pad or the nail apparatus, restitution is ad integrum.…”
Section: Management Of a Nail Avulsion In Emergencymentioning
confidence: 98%
“…Some authors simply insert a nail splint and leave the nail bed under spontaneous healing, without a graft. 26 We strongly believe that a careful and complete reconstruction of all involved structures is the guarantee for the best results. In our experience, in these cases where there is no loss of pad or the nail apparatus, restitution is ad integrum.…”
Section: Management Of a Nail Avulsion In Emergencymentioning
confidence: 98%
“…If the avulsed fragment is not available because of loss or destruction, conservative treatment or reconstructive techniques can be considered. Conservative techniques are based on the observation that the nail bed has a regenerative potential that allows for complete nail repair in about 6 weeks [ 17 ]. In his study, Ogunro [ 14 ] reported that when the residual nail bed is effectively covered, in order to prevent drying and maintain a local environment suited for tissue regeneration, normal nail growth may be obtained.…”
Section: Nail-bed Avulsion (Sterile and Germinal Matrix Defect)mentioning
confidence: 99%
“…Treatment of nail bed defects caused by nail bed disorders is a significant clinical challenge in hand surgery due to the lack of uniform nail bed thickness and distinct regenerative ability (Ogunro & Ogunro, 2007). Clinically, the area of nail bed defects is managed by replacing it with a split thickness nail bed graft, which is harvested from the adjacent nail bed when the defect is very small or from the great toe nail when the defect is large.…”
Section: Introductionmentioning
confidence: 99%